The Road to Batemans Bay - Greig, Alastair (ANU Press, 2024)
The Road to Batemans Bay is the story of competing ventures to create 'the Great Southern Township' on the South Coast of New South Wales in the early 1840s. The idea of developing the furthest reaches of settlement was linked to the hopes of southern woolgrowers for a road from their properties to the coast, over the Great Dividing Range. The township proponents dreamed that having a quicker and cheaper connection to Sydney would allow them to open a port second only to Port Jackson. The scene begins with the proposed coastal township of St Vincent, in an age of optimism: settlement is expanding, exports are growing and land prices are soaring, generating Australia’s first land boom. Before long, however, the colony experiences a catastrophic economic depression whose ‘pestilential breath’ infects those with a stake in the coastal townships. Alastair Greig follows the fate of these individuals, while also speculating on the broader fate of South Coast development during the mid-nineteenth century. Greig gives a unique insight into many aspects of colonial life—including the worlds of Sydney’s merchants, auctioneers, land speculators, surveyors, map-makers and lawyers—as well as its maritime challenges. The Road to Batemans Bay is a chronicle of how Australia first developed its land-gambling habit and how land speculation led to the road to ruin.